Smart Tourism Destinations : Integrating IoT for Enhanced Visitor Management - Sudarat Keyuraphan; Yingluck Shinawatra; Pita Limjaroenrat (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research focuses on the use of Internet of Things (IoT) technologies in creating smart tourism destinations. By implementing IoT sensors and devices for crowd management, energy efficiency, and visitor tracking, destinations can enhance operational effectiveness while delivering a seamless visitor experience. The paper also addresses challenges such as data privacy and cost.